The effect of training sections on the physical preparation of the qualities of ’strength and speed’ in football players (14-16) years old - Bedjaoui, Fadheli (sports creativity, 2025)
To arrive at a set of facts about the impact of team level on physical preparation, attempting to understand the underlying relationship between team level and players' physical preparation.